Leverage and performance: the case of the U.S. hospitality industry - Conrado Diego García-Gómez; Mehmet Huseyin Bilgin; Ender Demir; José María Díez-Esteban (Quantitative Finance and Economics, 2021)
This study analyzes the leverage and performance relationship in the context of the U.S. hospitality industry. We consider that, studying this traditional corporate finance issue in the context of the hospitality industry, is relevant due to its unique characteristics in terms of capital structure and value creation. In addition to Ordinary Least Squares (OLS) and Fixed-Random effects (FE-RE) estimations, we also employ System Generalized Method of Moments (GMM) panel data techniques to avoid the endogeneity issue. Thus, using a sample of 313 U.S. hospitality firms for the period 2001–2018, our primary results are consistent with the pecking order theory, suggesting a negative relationship between leverage and firm performance. The findings are robust to alternative variables description and econometric techniques. We also find an inverted U-shape relationship, but given the high indebtedness of hospitality firms, the negative impact on firm performance is prevalent. Our contribution to the literature is double. First, we highlight the importance of analyzing the capital structure issue in a certain industry and, second, we provide important policy implications for managers and investors.